2014
DOI: 10.1002/app.40652
|View full text |Cite
|
Sign up to set email alerts
|

Star‐shaped POSS–methacrylate copolymers with phenyl–triazole as terminal groups, synthesis, and the pyrolysis analysis

Abstract: Star-shaped polyhedral oligomeric silsesquioxane (POSS)-methacrylate hybrid copolymers with phenyl-triazole as terminal groups had been designed and synthesized via sequential atom transfer radical polymerization (ATRP), azidation, and phenylacetylene-terminated procedures, and the hybrid copolymers here could be denoted as POSS-(PXMA-Pytl) 8 , where X can be M, B, L, and S, represented four different methacrylate monomers, such as methacrylate (MMA), butyl methacrylate (BMA), lauryl methacrylate (LMA), and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The pyrolysis reactions often start with the halogen terminal group and then mainly attribute to chain depolymerization. 32,33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyrolysis reactions often start with the halogen terminal group and then mainly attribute to chain depolymerization. 32,33…”
Section: Resultsmentioning
confidence: 99%
“…The pyrolysis reactions often start with the halogen terminal group and then mainly attribute to chain depolymerization. 32,33 As shown in Table 2, it is found that the decomposition temperatures increase as the heating rate increases. Both T 1 and T 2 increase successively in the order of PMMA, PMMA-b-1PS, and PMMA-b-1.8PS at the same heating rate.…”
Section: Thermal Stability and Thermal Decomposition Kinetics Of The Copolymermentioning
confidence: 89%
“…Materials POSS-(Cl) 8 was synthesized and used as initiator, as described in a previous report [27]. All chemicals were of reagent grade and used as received, unless specified otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…95,96 In general, the syntheses of such polymer-POSS hybrids have been performed by using monofunctionalized POSS NPs as macro-initiators for living polymerizations [e.g., anionic, cationic, ring opening polymerization (ROP), nitroxide-mediated polymerization (NMP), reversible addition-fragmentation chain transfer (RAFT), atom transfer radical polymerization (ATRP)] and click chemistry. [97][98][99][100][101][102][103] For example, we used a chain-end-tethered mono-functionalized chloride-POSS as a macroinitiator to prepare a poly(methyl methacrylate)-block-POSS (PMMA-b-POSS) hybrid through ATRP [Fig. 3(a)].…”
Section: Self-assembly Of Chain-end-tethered Mono-functionalized Poss...mentioning
confidence: 99%